Sex-Based Differences in Age-Related Changes of the Vertebral Column from a Bronze Age Urban Population in Ancient China - Han, Tao; Zhang, Wenxin; Xie, Yaoting; Zhou, Xuyang; Zhu, Hong; Zhang, Quanchao; Wang, Qian (Anthropological Review, 2022)
The health disparities between males and females in bioarchaeological settings are important indicators of gender-based differences in socioeconomic roles. In this study, sex-based differences of the vertebral column in spine pathology were investigated in human skeletons excavated from a Bronze Age cemetery of the Western Zhou Dynasty at the Dahekou site in Shanxi, China. Results demonstrated that females had a higher prevalence of vertebral compressive fractures, with the majority found in those between twenty-five and thirty years old, suggesting that the fractures were a consequence of osteoporosis and its early onset in females. In contrast, males expressed overall more severe ageing in all vertebral divisions compared to females. Males also had a higher prevalence of vertebral facet joint osteoarthritis in cervical and thoracic divisions than females. Likewise, the incidence of facet joint osteoarthritis was more asymmetric between the left and right joints in males than in females. These findings reflect disparities of vertebral health between the two sexes in an urban setting, in which ageing and injuries of the vertebral column might be driven by different mechanisms. Age-related changes in female vertebral columns may have been more influenced by conditions of hormone deficiency such as menopause, while male vertebral columns might have been more prone to age-related changes due to heavy labor-induced physical stressors. Further studies on the differentiation of ageing mechanisms between the two sexes based on physiology, socioeconomic roles, and living conditions are warranted. The studies are necessary in understanding how multiple sociocultural and physiological factors contribute to health disparities in historic and contemporary environments.